Conceptualizing norm diffusion and norm contestation in the European neighbourhood: introduction to the special issue. Issue 3 (3rd April 2022) - Dandashly, Assem; Noutcheva, Gergana
ABSTRACT: The introduction to the special issue sets out to examine the normative rivalry between the European Union and other regional actors and how it plays out at the domestic level in the societies of the European neighbourhood. Drawing on the International Relations literature on norm diffusion, and in particular on the scholarship on norm contestation, we posit that the degree and nature of domestic contestation of external political norms (both EU and non-EU) has consequences for norm diffusion in specific domestic settings. We deepen the conceptual understanding of the encounter between external and domestic political norms by emphasizing the agency of domestic societies and the importance of domestic normative structures in the processes of acceptance, modification or rejection of external normative influence. We provide empirical evidence about competing normative influences collected from a plethora of case studies from the eastern and the southern European neighbourhoods allowing us to draw a cross-regional parallel about the political ideas more likely to gain traction in the societies of Eastern Europe and the Middle East and North Africa.